KONTEKSTUALISASI PEMAHAMAN HADIS TENTANG ZINA SEBAGAI TAKDIR: ANALISIS PEMIKIRAN IMAM AN-NAWAWI - Wicaksono, Dandy; Hasanah, Uswatun; Zulfikar, Eko (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
This article aims to discover the meaning of the hadith regarding adultery as a fate from Imam An-Nawawi's perspective. The use of hadith is directed at contextualizing contemporary meaning using a descriptive-analytical ma'ani al-hadith approach. Thus, this article concludes that Imam An-Nawawi's perspective on the hadith regarding adultery as destiny can be divided into two, namely adultery majazi (small) and adultery intrinsic (large). The meaning of the word destiny in adultery is not destiny as a concrete decree, but is a figure of speech so that Muslims are always careful to protect themselves. Imam An-Nawawi's view of the adultery hadith is in line with the current context, where the development of technology and information has provided an illustration of how difficult it is to protect all parts of the body from something that is forbidden. In this modern era, adultery can be found in various applications that display photos and videos easily. Fornication of hearing is also possible with just one click and various types of audio will appear, adultery of the heart by watching a video which then gives rise to feelings of wanting to commit immorality, which in the end will lead to real adultery. The hadith regarding adultery above shows that every act of adultery must be committed, and the private part will be the judge of whether it is genuine adultery or majazi, it all depends on the limits of the ability to restrain each individual's desires and desires.